Experiments in the control of Phytophthora infestans under the conditions of Pelotas and São Lourenço do Sul in Rio Grande do Sul, Brazil - Galli, José; Costa, Delorge Mota da; Liberal, Mozart Teixeira; Luzzardi, Gilberto Ceciliano; Tyler, Kent B.; Castro, Fernando Sereno de (Pesquisa Agropecuaria Brasileira, 2014)
The Plant Pathology and Horticulture Sections of the IPEAS, in collaboration with the IRI, have carried out eight experiments for comparison of fungicides in the control of Phytophthora infestans (Mont.) De Bary, the agent of the mildew of potato (Solanum tuberosum L.). The tests were made during the period from 1965 to 1967. All of the fungicides tested showed capacity for the control of the disease, even when a small number of applications were made. It was not possible to analyze statistically the combined data of production from all the experiments. Nevertheless, the phytopathological observations made during the course of the work made clear that there was a slight superiority of the fungicides Manzate D, Dithane M-45 and Miltox as compared with the other fungicides. Thus, it was demonstrated that the efficiency of presently available fungicides is adequate for use in chemical prophylactic treatment, however, it is conditioned by other factors that are described in the text and in previous research work.